INITIAL RESOURCE PROVISIONINGIN IAAS CLOUDS BASED ON THE ANALYTIC HIERARCHY PROCESS - Andrey A. Mikryukov (Statistika i Èkonomika, 2016)
The aim of this paper is to describe one possible solution of a problem of efficient initial resource provisioning in the Infrastructure-as-a-Service cloud environments using the Analytic Hierarchy Process.